Finite element investigation of the shear performance of corroded RC deep beams without shear reinforcement - Nguyen, Trung Kien; Nguyen, Ngoc Tan (Case Studies in Construction Materials, 2021)
The shear behavior of reinforced concrete (RC) beams has been the principal subject of research studies. However, the structural behavior of RC deep beam without shear reinforcement is still complex and not well-understood. A total of sixteen corroded deep beam specimens without shear reinforcement were investigated in this numerical study. The finite element results confirm the validity of the developed constitutive models by comparing load - displacement curves and failure modes obtained in two experimental studies. It showed that the corrosion of longitudinal reinforcement decreased the load-carrying capacity and has shifted the load-transferring mechanism of corroded deep beams vastly, from combining arch and beam action to a more dominant arch action. Finally, a parametric study of corroded RC deep beam having no shear reinforcement is performed based on various parameters, i.e., degree of corrosion, bond reduction, anchorage condition, shear span-to-depth ratio. The obtained results show a considerable contribution of the corroded deep beam having sufficient anchorage provisions on the load-carrying capacity of beam specimens. Moreover, the shear span-to-depth ratio and corrosion degree do not always bring adverse effects on the failure mode, and shear resistance mechanism of corroded deep beams. •A total of sixteen corroded deep beam specimens without shear reinforcement were simulated and investigated.•Longitudinal reinforcement corrosion has shifted the load-transferring mechanism of deep beams without shear reinforcement.•Sufficient anchorage provisions in the corroded deep beam show a considerable contribution to the shear performance.